Implementation of Fulfillment of Children's Rights Post-Divorce in the Jombang Religious Courts - Maghfuri, Muhammad Zainul; Al-Amin, Habibi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The issue of fulfilling children's rights after divorce has become an important study of researchers in the field of Islamic law over the past five years. The issues of fulfilling children's rights after divorce have become a serious problem, where children's rights are often overlooked, especially with regard to basic rights. In this study, there are 2 (two) problem formulations that are the focus of this research. First, the implementation of the fulfillment of children's rights after divorce based on decision No. 3118/Pdt.G/2021/PA.Jbg, Second, the efforts that must be taken by the mother if the decision on children's rights after divorce is not fulfilled by the ex-husband (father). research and discussion that has been analyzed. In this case, it does not fully reach the target, the mother is fully trying alone to fulfill the rights of the child where the ex-husband (father) should have played a role but did not maximally carry it out as stated in the decision. Then the legal consequences for the ex-husband who does not carry out his obligations in fulfilling child maintenance, the mother can submit a child maintenance lawsuit to the Chairman of the Religious Court for further execution. Because the law itself does not regulate the existence of legal sanctions against decisions that have been condemned when not implemented. So that it becomes an obstacle for the mother not to submit a request for execution for several reasons: the former husband (father) remarried, the mother is able to finance child maintenance independently and lack of knowledge about the law.